Exploring differences between TTO and direct choice in the valuation of health states - Angela Robinson; Anne Spencer; Jose-Luis Pinto-Prades; Judith Covey (University of East Anglia, Health Economics Group (HEG), 2015)
There is recent interest in using Discrete Choice Experiments (DCEs) to derive health state utility values and results can differ from Time Trade Off (TTO). Clearly DCE is 'choice-based' whereas TTO is generally considered to be a 'matching' task. We explore whether procedural adaptations to the TTO -which make the method more closely resemble a DCE -makes TTO and choice converge. In particular, we test whether making the matching procedure in TTO less 'transparent' to the respondent reduces disparities between TTO and choice. We designed an interactive survey that was hosted on the internet and 2022 interviews were achieved in the UK. We found a marked divergence between TTO and choice, but this was not related to the 'transparency' of the TTO procedure. We conclude that a combination of insensitivity in the TTO (however conducted) and factors other than differences in utility affecting choices is driving the divergence.
Keywords: 330; Utility assessment; Matching; Choice; EQ-5D 5L; DCE; TTO